1960
DOI: 10.1172/jci104071
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Factors Affecting Airway Resistance in Normal Subjects and in Patients With Obstructive Respiratory Disease*

Abstract: Although the airway conductance1 increases at larger lung volumes in normal subjects (1), it is reduced in patients with asthma or emphysema who are breathing with a large functional residual capacity (FRC) (2). We have therefore tried to assess the influence of other factors which might affect the airway conductance in both normal subjects and in patients with asthma, bronchitis and emphysema. These include the interrelationship of lung volume, lung elastic pressure and airway conductance, the effect of exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
1
1

Year Published

1970
1970
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(93 citation statements)
references
References 9 publications
10
81
1
1
Order By: Relevance
“…On theoretical grounds, however, it is possible to visualize situations where changes in maximum expiratory flow occur without there being a change in airways resistance measured in the body plethysmograph, or conversely, where changes in resistance do not result in a change in maximum expiratory flow. A striking example of this type of discrepancy has been observed in normal subjects after the inhalation of isoproterenol, in whom it has been shown that, despite a considerable fall in airway resistance and rise in anatomical dead space (1)(2)(3)(4), there is very little change in the FEV1 (4). In the present study we have examined in detail the alterations in pulmonary mechanics that occur in normal subjects after isoproterenot in an effort to determine the causes of this particularpattern of change.…”
Section: Introductionmentioning
confidence: 85%
“…On theoretical grounds, however, it is possible to visualize situations where changes in maximum expiratory flow occur without there being a change in airways resistance measured in the body plethysmograph, or conversely, where changes in resistance do not result in a change in maximum expiratory flow. A striking example of this type of discrepancy has been observed in normal subjects after the inhalation of isoproterenol, in whom it has been shown that, despite a considerable fall in airway resistance and rise in anatomical dead space (1)(2)(3)(4), there is very little change in the FEV1 (4). In the present study we have examined in detail the alterations in pulmonary mechanics that occur in normal subjects after isoproterenot in an effort to determine the causes of this particularpattern of change.…”
Section: Introductionmentioning
confidence: 85%
“…However, we suggest that the physiology described is unlikely to be the major determinant of the SLS phenotype. As Dr. Eberlein notes, impairment of compliance by chest strapping is quickly reversed -a few deep breaths are sufficient to restore normal compliance measures 3,4 . This was not the case with our patients with SLS, in whom compliance remained low through the course of pulmonary testing that included maximal respiratory efforts.…”
Section: To the Editormentioning
confidence: 99%
“…The static conditions under which the interdependence was assessed by NOBLE et al [289] do not represent the real environfment of the lung [297]. The viscoelastic lung parenchyma under dynamic conditions interacts with the airways very differently [298,299], and this should be kept in mind if the experiments of NOBLE et al [289] are revisited.…”
Section: Parenchyma-airway Interdependencementioning
confidence: 99%